Književna esejistika in književna kritika - Štuhec, Miran (Slavistična revija, 2013)
The aim of this article is to show how recent Slovene literary scholarship has assessed literary criticism and the practice of the literary essay. The chief finding confirms the assumption that in the past decade and a half there have been many works that significantly expand previous historical and theoretical understandings. If other scholarly events are included, it is possible to conclude that literary scholarship vigorously and competently reflected upon both forms.
Keywords: axiology; esejistika; history of the essay; književna kritika; literary criticism; literary essay; Slovene literary history; Slovene literary studies; Slovene literature; slovenska književnost; slovenska literarna veda; slovenska literarna zgodovina; vrednotenje; zgodovinski pregledi